Successful baricitinib treatment of refractory anti‐synthetase syndrome associated with interstitial lung disease. Issue 4 (22nd March 2023) - Sugino, Keishi; Ono, Hirotaka; Saito, Mikako; Ando, Masahiro; Tsuboi, Eiyasu
Abstract: A 47‐year‐old Japanese man was admitted with dyspnoea on exertion (DOE), skin rash and myalgia. Clinical findings of Gottron's sign and mechanic's hands were observed, with increased serum levels of Krebs von den Lungen‐6, surfactant protein‐D, creatine kinase, and anti‐EJ on laboratory tests. In both lungs, chest computed tomography revealed diffuse reticular opacities and lower lobe predominance. The patient was diagnosed with anti‐synthetase syndrome (ASS) and associated interstitial lung disease. Despite repeated administration of high‐dose intravenous corticosteroids, cyclophosphamide and immunoglobulin, his skin rash, myalgia, and DOE followed a relapsing and remitting course. He was then given rituximab therapy. This was initially successful, but disease activity increased approximately 12 months after starting rituximab therapy. Finally, in addition to prednisolone and cyclosporine A, we administered baricitinib. There has been no relapse of the disease in the 12 months since he began baricitinib treatment. Abstract : Interstitial lung disease (ILD) in patients with anti‐synthetase syndrome (ASS) is often a severe and progressive disease that requires a lengthy treatment course involving multiple agents. We present a case of refractory ASS‐ILD successfully treated with baricitinib after the failure of several other treatments. Bariticinib shows promise as a salvage treatment for patients with refractory ASS‐ILD.